APPLIED GEOTECHNOLOGY TOOBTAININGTHE CHARACTERISTICS OF LAND USE CAPACITY SUBCLASSES A WATERSHED, AIMINGTHE CONSERVATION OF NATURAL RESOURCES. - Campos, S.; Campos, M.; Nardini, R.C.; Rodrigues, B.T.; Rodrigues, M.T.; Tagliarini, F.S.N.; Traficante, D.P. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The exploitation of the land to food produce for human consumption was almost always in a disorderly manner and without planning. The result of thispredatory exploitation was the soil impoverishment by intense erosion, siltation of water bodies, desertification, andothers. In this study it was usedgeotechnology fordevelopment of slope classes maps, soil and land use capacity in a watershed, in order tocontributein the environmental management process and in Public Administratorsdecision-making. The Agulhas stream watershed, Botucatu(SP) has an area of 1429.28ha and is situatedbetween thegeographic coordinates22o47'05" to 22o05'55" S and 48o28'10" to 48o30'04" WGr. The result showsthat subclass IIIs,e(44.50%) and undulated relief areas (57.59%) the most significant. Theuse capacity subclasses IIIs, IIIs,e and IVs occupied 89.36% of the area, showing the great potential of use for annual crops , perennials, pastures and reforestation. The Geographic Information System (GIS) proved to be an excellent tool for determining the land use capability, demonstrating that the use of GIS facilitates and faster at the intersection of digital data, allowing storage, which can be used for other analysis in future geo-environmental planning.